(untitled) (Editora Impacto Científico, 2025)
This study evaluated sustainability in Food and Nutrition Units (FNUs) as an ethical and managerial imperative aimed at conserving natural resources. Sustainability involves minimizing environmental impact through waste management, conscious purchasing, and resource efficiency. Research, based on checklists using international standards (ISO, SRA, GRA), shows that although FNUs adopt sustainability practices, the adequacy percentage is partial (between 36.4% and 54.5%), indicating the urgency of implementing more rigorous requirements. The main challenges include high generation of organic waste in pre-preparation, high rates of ready-made food waste, and failures in the Good Environmental Practices blocks (Water, Waste, and Documentation). It is concluded that the FNU requires continuous and integrated management that transcends the basics, where the Nutritionist is essential to convert the team’s environmental awareness into operational excellence and improve planning to reduce losses and consolidate socio-environmental responsibility. DOI: https://doi.org/10.56238/edimpacto2025.090-035